2013
DOI: 10.1007/s10815-012-9929-1
|View full text |Cite
|
Sign up to set email alerts
|

Single thawed euploid embryo transfer improves IVF pregnancy, miscarriage, and multiple gestation outcomes and has similar implantation rates as egg donation

Abstract: STEET results in a high pregnancy rate, low multiple gestation rate and miscarriage rates. Despite the older age of STEET patients and transfer of twice as many embryos, the implantation rate for STEET was indistinguishable from that for egg donation. STEET offers an improvement to IVF, lowering risks without compromising pregnancy rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 45 publications
1
55
0
Order By: Relevance
“…In turn, this increases the chance for implantation and decreases the likelihood of miscarriage associated with aneuploidy [14,19]. Being able to select the euploid embryo that has higher implantation potential will allow us to limit the numbers of embryos transferred per cycle, thereby decreasing the chance of twins and high order multiple gestation while increasing overall pregnancy rate [20]. Other studies have also shown that implantation rates remain similar regardless of maternal age following embryo biopsy and PGS when only euploid embryos were transferred [3,21].…”
Section: Introductionmentioning
confidence: 99%
“…In turn, this increases the chance for implantation and decreases the likelihood of miscarriage associated with aneuploidy [14,19]. Being able to select the euploid embryo that has higher implantation potential will allow us to limit the numbers of embryos transferred per cycle, thereby decreasing the chance of twins and high order multiple gestation while increasing overall pregnancy rate [20]. Other studies have also shown that implantation rates remain similar regardless of maternal age following embryo biopsy and PGS when only euploid embryos were transferred [3,21].…”
Section: Introductionmentioning
confidence: 99%
“…The odds ratios for patients with 3 and 4 available euploid embryos were 1.15 and 1.36 yielding probabilities of clinical pregnancy of 0.54 and 0.58. In order to maintain a live birth rate of roughly 50 % (accounting for roughly 10 % rate of pregnancy loss from euploid transfers [29,30] from a 58 % clinical pregnancy rate) we chose to set the threshold at 4 euploid embryos. Patients were stratified by the number of euploid blastocysts produced (≤3 vs ≥4), as well as the number of embryos transferred (1 vs 2).…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies have shown that highly graded embryos can be chromosomally abnormal [13,14,15,16] and aneuploidy is the leading cause of failed implantation and miscarriage [17,18,19,20,21,22,23]. While initial attempts at preimplantation genetic screening (PGS) in cleavage stage embryos failed to demonstrate improved pregnancy rates, trophectoderm biopsy coupled with comprehensive chromosomal screening (CCS) [24,25] have yielded encouraging results [26,27,28,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Elective single blastocyst embryo transfer has been shown to have equivalent implantation and pregnancy rates compared to double embryo transfer while significantly reducing the rate of twin gestations [16]. Emerging technology like preimplantation genetic screening (PGS) is used to select a single euploid embryo for transfer, therefore, improving pregnancy rates and decreasing the miscarriage rate due to aneuploidy [17][18][19][20]. PGS relies more on blastocyst-stage biopsies which pose less risk of damage to the embryo and allow for the genetic analysis of a greater number of cells reducing the risk of misdiagnosis secondary to mosaicism [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%